224k views
4 votes
Enter the values for the highlighted variables to

complete the steps to find the sum:
az
b =
3x 9
+
2x - 6 6 - 2x
CE
d =
3 x
9
+
2x-6 al 2x-6)
3x b.
+
2x-6 2x - 6
3х – с
2x-6
d{x - e)
f(x-3)
= 9
e =
f=
III
g=
DONE

Enter the values for the highlighted variables to complete the steps to find the sum-example-1
User Sorceror
by
4.6k points

1 Answer

5 votes

Answer:

a = - 1

b = - 9

c = 9

d = 3

e = 3

f = 2

g = 3/2

Explanation:

For a;

6 - 2x = - (2x - 6)

For b;

-1 * 9 = - 9

For x ;

3x + (-9) = 3x - 9

3x - 9 = d(x - e)

Factorizing :

3(x - 3)

d = 3 ; e = 3

2x - 6 = f(x - 3)

Factorize :

2x - 6 = 2(x - 3)

3(x - 3) / 2(x - 3)

g = 3/2

User Webbiedave
by
5.6k points